2009
DOI: 10.5194/nhess-9-197-2009
|View full text |Cite
|
Sign up to set email alerts
|

Hazard index maps for woody material recruitment and transport in alpine catchments

Abstract: Abstract.A robust and reliable risk assessment procedure for hydrologic hazards deserves particular attention to the role of transported woody material during flash floods or debris flows. At present, woody material transport phenomena are not systematically considered within the procedures for the elaboration of hazard maps. The consequence is a risk of losing prediction accuracy and of underestimating hazard impacts. Transported woody material frequently interferes with the sediment regulation capacity of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 24 publications
(22 reference statements)
0
79
0
Order By: Relevance
“…Nevertheless, wood in-channel could be a threat to some human activities on rivers, including disruption of the navigation on large rivers and commercial marine operations (Piégay, 2003). Moreover, if wood is transported massively during highmagnitude flood events, it could represent a risk for sensitive structures such as bridge piers (Mazzorana et al, 2009;Rigon et al, 2012). Given the important positive and potentially very negative effects of wood in rivers, increasing attention has been given to the assessment of wood budget at the catchment and reach scales (Sedell and Froggatt, 1984;Palik et al, 1998;Piégay et al, 1999;Marcus et al, 2011;Schenk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, wood in-channel could be a threat to some human activities on rivers, including disruption of the navigation on large rivers and commercial marine operations (Piégay, 2003). Moreover, if wood is transported massively during highmagnitude flood events, it could represent a risk for sensitive structures such as bridge piers (Mazzorana et al, 2009;Rigon et al, 2012). Given the important positive and potentially very negative effects of wood in rivers, increasing attention has been given to the assessment of wood budget at the catchment and reach scales (Sedell and Froggatt, 1984;Palik et al, 1998;Piégay et al, 1999;Marcus et al, 2011;Schenk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies like Mazzorana et al (2009), emphasize the importance of a qualitative and quantitative assessment of woody debris recruitment and transport during flood events. However, for this study no data on woody debris yield to the fan is available, so test cases including woody debris are based on rough estimates.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of recent flood events documented in the Province of Bolzano showed that wood vegetation in the river bed has a higher relative tendency to produce woody material (depending on wood stand volume) compared to wood vegetation on stream banks. In absolute terms, the amount of woody material recruited from the stream banks exceeded the volume recruited from the riverbank (Mazzorana et al 2009). This fact can be attributed to the wood stand volume being on average larger on the bank slopes than in the river bed.…”
Section: Woody Materials Recruitmentmentioning
confidence: 99%
“…These wood-covered areas within a buffer width are categorised as active wood buffer (AWB) areas. This buffer width corresponds either to the potential tree height derived from the forest typology map (Klosterhuber et al 2007) or to the real tree height retrieved from the Lidar-based digital surface model and the digital terrain model (Mazzorana et al 2009). The difference between the surface model and the terrain model can give hints about the reference tree height and therefore about the width of the active wood buffer.…”
Section: Assessment Of the Recruitment Volumes From Hill Slopesmentioning
confidence: 99%
See 1 more Smart Citation